2022
DOI: 10.11591/ijeecs.v29.i1.pp518-526
|View full text |Cite
|
Sign up to set email alerts
|

Proposed security mechanism for preventing fake router advertisement attack in IPv6 link-local network

Abstract: The design of router discovery (RD) is a trust mechanism to confirm the legitimacy of the host and router. Fake router advertisement (RA) attacks have been made possible by this RD protocol design defect. Studies show that the standard RD protocol is vulnerable to a fake RA attack where the host will be denied a valid gateway. To cope with this problem, several prevention techniques have been proposed in the past to secure the RD process. Nevertheless, these methods have a significant temporal complexity as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…To handle and keep track of the electrical appliances in the house, they developed two smart contracts. Users can send messages to the IoT gadgets in their homes using their mobile phones [33]. Additionally, Outchakoucht et al [34] suggested an access control system for IoT, or the IoT the smart contracts on the blockchain are where the access control method is laid forth.…”
Section: Global Access Controlmentioning
confidence: 99%
“…To handle and keep track of the electrical appliances in the house, they developed two smart contracts. Users can send messages to the IoT gadgets in their homes using their mobile phones [33]. Additionally, Outchakoucht et al [34] suggested an access control system for IoT, or the IoT the smart contracts on the blockchain are where the access control method is laid forth.…”
Section: Global Access Controlmentioning
confidence: 99%
“…Fake news was recently defined as "intended and verifiably false news articles which misinform the audience" [5], [27]- [29]. Due to its interruptive and disappointing nature, as alleged by scientists and professionals, the term "fake news" has garnered somewhat less attention [30], [31].…”
Section: Background 31 Fake News Definition and Typesmentioning
confidence: 99%
“…The internet of things (IoT) is one of the most talked-about innovations because of the numerous benefits it could bring to modern life. As the IoT continues to advance, an increasing number of objects in our surroundings will be able to connect to the Internet and communicate with one another automatically, without any intervention from humans [1], [2]. The original motivation behind the IoT was to eliminate the need for manual data entry by replacing it with a network of interconnected devices equipped with sensors to collect data from their surroundings.…”
Section: Introductionmentioning
confidence: 99%